2015
DOI: 10.1111/iju.12866
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of lower urinary tract symptoms/benign prostatic hyperplasia surgical treatments on men's ejaculatory function: Time for a bespoke approach?

Abstract: Although ejaculatory dysfunction is common for patients undergoing benign prostatic hyperplasia surgery, no clear evidence is present to counsel men seeking to preserve ejaculation. Our aim was to evaluate ejaculatory dysfunction in relation to benign prostatic hyperplasia surgery. We carried out a web and manual search using MEDLINE and Embase including randomized controlled trials reporting ejaculatory dysfunction after benign prostatic hyperplasia surgery: 42 randomized controlled trials comprising a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 67 publications
(267 reference statements)
7
47
0
6
Order By: Relevance
“…The AUA BPH guideline panel estimates the incidence of of EjD with TURP at 65% (2). Consistent with this a review of 30 RCTs involving TURP showed the rate of EjD at 66.1% (8). It must be appreciated however that pre-operative ejaculatory dysfunction is common in men undergoing TURP being estimated around 30–35%.…”
Section: Effect Of Bph Treatments On Ejaculatory Functionsupporting
confidence: 55%
“…The AUA BPH guideline panel estimates the incidence of of EjD with TURP at 65% (2). Consistent with this a review of 30 RCTs involving TURP showed the rate of EjD at 66.1% (8). It must be appreciated however that pre-operative ejaculatory dysfunction is common in men undergoing TURP being estimated around 30–35%.…”
Section: Effect Of Bph Treatments On Ejaculatory Functionsupporting
confidence: 55%
“…A recent systematic review by Marra et al [21] has evaluated the impact of all actual surgical techniques for BPH treatment on ejaculatory function. The ‘dry orgasm' because of the retrograde flow of semen is considered an afterthought by clinicians counselling patients before BPH surgery, even if a rising interest for ejaculation preservation is in the process of being developed.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual function is increasingly recognized and measured as an important primary outcome. Furthermore, research has shown erectile dysfunction to have a greater impact on quality of life than LUTS [Marra et al 2015]. As such, the development of UroLift should be praised in identifying this therapeutic void and acting upon it.…”
Section: Further Considerations and Potential Limitationsmentioning
confidence: 99%